Perilaku Menyakiti Diri Sendiri Bentuk, Faktor dan Keterbukaan Dalam Perspektif Perbedaan Jenis Kelamin - Rini, Rini (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2022)
Self-harm is perpetrated by both men and women. Comparison of the types, factors and disclosures of self-harm based on the perspective of gender differences need to be researched more. The aim is to get an idea of the differences in types, factors and disclosures between men and women in terms of self-harm. Respondents in this study were 348 people who had done self-harm with accidental sampling technique. Data is collected by google forms which are distributed via social media. Data analysis using descriptive approach. The results of the analysis show that the most common types of self-harm by women are pulling their hair and hitting themselves, while men are more likely to hit themselves. The women’s self-harm is more triggered by factors of not being able to control their emotions and factors of low self-esteem and loneliness. While many men are triggered by factors of not being able to control their emotions and cannot solve problems or cannot achieve what is expected. Both men and women have a propensity to cover up their selfharming from anyone. However, in terms of choosing to tell about their self-harm to some closest people, women have a tendency to disclosure up 6 times higher than men